The Cosmic Evolution and Spatial Distribution of Multiphase Gas Associated with QSOs - Zeyu Chen; Enci Wang; Hu Zou; Haoran Yu; Zhicheng He; Huiyuan Wang; Yang Gao; Cheqiu Lyu; Cheng Jia; Chengyu Ma; Weiyu Ding; Runyu Zhu; et al. (The Astrophysical Journal Letters)
We investigate the multiphase gas surrounding QSOs traced by 33 absorption lines (e.g., Ly α , C iv , Fe ii , Mg ii , etc.) in the stacked spectra of background sources, using the Early Data Release from the Dark Energy Spectroscopic Instrument. Our analysis reveals that the equivalent width ( W ) of metal absorption lines decreases with increasing redshift, following an overall trend described by W  ∝ (1 +  z ) ^−4.0±2.7 . Different species that trace multiphases of QSO-associated gas exhibit distinct evolutionary patterns. Additionally, the W of these absorption lines decreases with distance ( D ) from QSOs, which can be effectively characterized by a two-halo model. Compared to the projected two point correlation function of galaxies at similar redshifts, low-ionization ions exhibit similar clustering scales, while high-ionization ions show a significantly more extended spatial distribution. We also find that W _FeII / W _MgII increases toward lower redshifts, which can be attributed to evolving star formation histories and/or changes in initial mass function for galaxies. By leveraging multiple absorption tracers, we conduct the first comprehensive investigation of diffuse, multiphase gas from the circumgalactic medium to cosmological scales, offering new insights into baryon cycles and the transport of metals throughout cosmic time.